Planning and installing solar thermal systems : a guide for installers, architects, and engineers (James & James/Earthscan, 2005)
"This book offers clear guidance on planning and installing a solar thermal system, crucial to the successful uptake of this technology. All major topics for successful project implementation are included. Beginning with resource assessment and an outline of core components, this guide covers solar thermal system design, installation, operation and maintenance for single households, large systems, swimming pool heaters, solar air and solar cooling applications. Details on how to market solar thermal technologies, a review of relevant simulation tools and data on selected regional, national and international renewable energy support programmes are also provided." "In short, the book offers comprehensive guidance for professionals who wish to install solar thermal technology and will be a cherished resource for architects and engineers alike who are working on new projects, electricians, roofers and other installers, craftsmen undertaking vocational training and anyone with a specialized and practical interest in this field."--BACK COVER.